My flowers bloomed at 12 a.m.! / Tuan Sarifah Aini Syed Ahmad - Syed Ahmad, Tuan Sarifah Aini (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Last week, I was very excited to wait for the bloom of my flowers at midnight. The flowers are known as bakawali. I have one pot of bakawali plants on my porch. It has flattened green stems or leaves. Its white flowers sprout from the stems several times a year. The flowers smell sweet like vanilla. When the flowers bloom, I could see some small black ants on the petals. I got more excited last week because there were more flowers than before. Bakawali actually belongs to the cactus family. Thus, it is easy to take care of. It does not need fertilizers and frequent watering. If you forget to water it, it will not die, but the colour of the stems turn into red. When the plant gets sufficient water, the stems turn into green again. You do not have to worry if you forget to water it for weeks, it still can survive because it is a cactus! If you want to plant it, just cut the stem since it does not produce fruits. Put it in a pot and water it until it grows bigger.